Sifat Organoleptik Sate Daging Entog dengan Teknik Marinasi Ekstrak Buah Nanas - Nazwa Alkhawaritsmy, Mochammad; Falahudin, Aaf; Imanudin, Oki (Tropical Livestock Science Journal, 2025)
This research aims to analyze acceptability by measuring the formulation for adding the best pineapple extract to Muscovy Muscovy meat. This research was conducted at the Faculty of Agriculture, Majalengka University on 2-16 September 2024. This research was carried out experimentally based on a completely randomized design (RAL) with 4 treatments and 5 replications. The results of the research show that the addition of pineapple extract to muscovy meat can affect the color, taste and acceptability. The conclusion of this research is that marinating pineapple fruit extract, pineapple fruit extract has an effect on color, taste and acceptability (p<0.05) but has no real effect on juices and texture (p>0.05), the conclusion of this research is: the addition of fruit extract Pineapple affects the acceptability of Muscovy Muscovy meat satay, treatment P1 with (10 ml) pineapple fruit extract / 100 g Muscovy Muscovy meat is the best treatment.